Manajemen Supervisi Akademik Kepala Sekolah Dalam Meningkatkan Profesionalisme Guru Pendidikan Agama Islam - Muhamad Faizin (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study is to examine the problems of planning, implementing, evaluating the principals in improving the professionalism of teachers Islamic Religious Education through academic supervision, the effectiveness of academic supervision in improving professionalism and the role of principal as a supervisor in improving the professionalism of teachers Islamic Religious Education at SMKN 14 and 15 Bandung. The basic concept in this research used Terry's theory of management science, E Mulyasa about professional teacher and S. Arikunto about academic supervision. The research method used in this research is descriptive method with qualitative approach and techniques of collecting the data which are used in this research are by observation, interview, and documentation. The data which are used are primary data by using observation, interview and direct documentation to the Principal the Vice Principal of Curriculum and for an additional information is Islamic Religious Education Teachers at SMKN 14 and SMKN 15 Bandung. The result of the research showed that the management guidance of principal through academic supervision is very influential in improving the professionalism of teachers Islamic Religious Education. So that remember the professionalism of Islamic Religious Education Teachers is influenced by the Principal's Academic Supervision, this is need to be improved, not only for Islamic Religious Education teachers but also for all of the teachers in the school